AN INVESTIGATION OF SONG-BASED LANGUAGE TEACHING ON TENSES LEARNING - Asfi Aniuranti (Economics, Social, and Humanities Journal (Esochum), 2021)
Grammar is one of the essential components in English that contains many elements like tenses. English tenses commonly become a problem among Indonesian students. Every English teacher, therefore, is required to provide creative and effective ways of teaching English tenses. This research aimed at investigating the benefits of English songs as teaching devices, the considerations in using English songs, and the teaching procedures. For the third variable, the researcher only focuses on the most frequently used tenses named present simple. The method employed was descriptive qualitative, and the researchers did this current study through three phases. They are data gathering, data analysis, and data presentation. This study reveals several significant findings. Firstly, English songs have many benefits called creating a positive learning environment, motivating the students, giving cultural information, and teaching linguistics knowledge. Secondly, there are at least five considerations in using English songs as teaching devices. They are the teaching topics, language level, student age, cultural issue, and song accessibility. Thirdly, there are three essential teaching procedures. They are warm-up activity, main activity, and additional activity. Overall, English songs are useful teaching devices in the EFL context, and they can effectively be used to teach language elements like tenses.